Pengembangan Media Pembelajaran Aplikasi ICARUS Untuk Mendukung Pembelajaran Matematika Di SDN 81 Kota Bengukulu - Firmansyah, Suandi; Supriatna, Irfan; Amaliyah, Yuli (JURIDIKDAS, 2026)
This research aims to develop a learning media in the form of the ICARUS (Interactive Creative Active Relevant Understanding Shape) application for plane geometry material as an effort to support mathematics learning for fourth-grade students at State Elementary School 81 Bengkulu City. This research is a Research and Development (R&D) study using the ADDIE development model. The research was conducted in 5 stages: analysis, design, development, implementation, and evaluation, carried out through small-scale trials to measure teacher and student responses. The instruments used were product validation sheets, teacher response questionnaires, and student response questionnaires. The feasibility of the ICARUS application was obtained through validation results conducted by four competent expert validators, including material experts, language experts, and graphic design experts. The validity of the ICARUS application learning media was obtained based on Aiken's V calculation results with an average material validity value of 0.96, language 0.86, and graphic design 0.93, all of which fall into the "very valid" category. Reliability testing using Percentage Agreement (PA) showed an agreement percentage above 80% with a strong agreement level, proving the consistency of assessments among validators and the reliability of the validation instrument. The practicality percentage value of the ICARUS application through teacher responses was 97.3% and student response results were 92.96% with an overall average of 95.13%, falling into the "very practical" category. The validation and small-scale trials through teacher and student responses indicate that the ICARUS application is highly valid and suitable for use as a mathematics learning media for plane geometry material in elementary schools.